2016
DOI: 10.21037/jtd.2016.11.100
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve implantation (TAVI) versus sutureless aortic valve replacement (SUAVR) for aortic stenosis: a systematic review and meta-analysis of matched studies

Abstract: The present study supports the use of minimally invasive SUAVR as an alternative to TAVI in high risk patients requiring aortic replacement. The presented results require further validation in prospective, randomized controlled studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Several meta-analyses reported higher postprocedural or 30-day mortality rates with TAVR group than with SU-AVR. 13 20 21 Similarly, in the present study, the TAVR group showed a trend towards a higher 30-day mortality than the SU-AVR group. However, there was no difference in cardiovascular mortality.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Several meta-analyses reported higher postprocedural or 30-day mortality rates with TAVR group than with SU-AVR. 13 20 21 Similarly, in the present study, the TAVR group showed a trend towards a higher 30-day mortality than the SU-AVR group. However, there was no difference in cardiovascular mortality.…”
Section: Discussionsupporting
confidence: 80%
“… 4 Furthermore, few studies have directly compared TAVR versus SU-AVR for severe AS. 13 Therefore, this study sought to compare early and late outcomes of TAVR versus SU-AVR for symptomatic severe AS in a single-center cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of AI have remained, however, between 2.2-10.3% (38)(39)(40)(41)(42). The use of a sutureless prosthesis via a surgical approach has not resulted in an increased incidence of postoperative AI, with rates remaining under 1% (43). The ability to surgically resect the diseased valve leaflets and decalcify the aortic annulus prior to insertion of a prosthetic valve may be a critical factor in ensuring low rates of AI.…”
Section: Tavi Large Randomized Trials Comparing Tavi To Savrmentioning
confidence: 99%
“…A number of studies have shown significantly higher rates of permanent pacemaker implantation with TAVI compared to sutureless AVR with the Perceval (14,26). However, these findings have not been reproduced consistently, and recently published systematic reviews and meta-analyses suggest that there is no significant difference in the rate of permanent pacemaker implantation between these technologies (9,27). These findings should be interpreted in light of the fact that self-expanding TAVI devices are associated with higher rates of conduction disorders than balloonexpandable devices (28).…”
Section: Sutureless Avr Versus Tavimentioning
confidence: 99%